PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, KEPUTUSAN INVESTASI, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan KOMPAS100 yang Terdaftar di Bursa Efek Indonesia (BEI) pada Tahun 2021-2023) - Yolanda Agneta Muljono; Abdul Rohman (Diponegoro Journal of Accounting, 2025)
This study aims to determine how the simultaneous and partial influence of capital structure (DER), company size (SZE), investment decisions (PER), and dividend policy (DPR) on company value (PBV). The independent variables analyzed include capital structure (Debt to Equity Ratio), company size (Ln total assets), investment decisions (Price Earnings Ratio), and dividend policy (Dividend Payout Ratio), while the dependent variable is company value as measured by the Price Book Value (PBV) proxy.This study uses quantitative data. The research method used in this study is purposive sampling. Secondary data used in this study were obtained from the Bloomberg Terminal database, company annual reports, and company annual financial reports. The samples used in this study were companies included in the KOMPAS100 index and listed on the Indonesia Stock Exchange in 2021-2023. Based on the established criteria, the final sample size was 117 research samples with 43 companies after removing outliers. Data analysis was conducted using the multiple linear regression analysis method using Statistical Product and Service Solutions (SPSS) 27 software.Based on the results of the regression analysis carried out, it can be concluded that the variables of capital structure, company size, investment decisions, and dividend policy have a positive and significant influence on company value. This finding indicates that internal company factors are important in increasing the market perception of company value.